Design Today: from the Virtual Space to the Objective and Environmental Reality - Efimov, Andrey (project baikal, 2017)
The article reviews the monography “Design today: from the virtual space to the objective and environmental reality. Design school in Irkutsk” written by O. Zheleznyak and her co-authors. The researchers focus on the urgent problem of the contemporary design concerning the interrelation between the virtual space and the objective and environmental reality. Design is interpreted as a system of identification of the region and branding of the city through discussion of the peculiarities of the image of the territory and regional trends in design. The same technique is used for featuring the image design in the virtual and material space. The monography provides the examples of scientific and design works elaborated by the Design Department of Irkutsk National Research Technical University.
Keywords: virtual; real; digitalization of professional awareness; art and design culture; design; identity; image; school of design